The Situation of CEE Economies after the COVID-19 Crisis - Becsey Zsolt László (Acta Universitatis Sapientiae: European and Regional Studies, 2022)
Written in late summer of 2022, this article aimed to provide an overview on the intra-EU cohesion of the EU Member States that transformed the communist system into a democratic market economy in 1988–90. The study analyses the economic background of these states for sustainable catching-up in the European Union. The result is a picture of a divided CEE area, where some states showed macroeconomic imbalances and economic growth, while others started to catch up with the solid background of the eurozone membership or its future perspective. In terms of most parameters, Hungary is in the first group but – together with Romania – is also facing serious macroeconomic difficulties.